THE APPLICATION OF PROJECT-BASED LEARNING USING MIND MAPS TO IMPROVE STUDENTS’ ENVIRONMENTAL ATTITUDES TOWARDS WASTE MANAGEMENT IN JUNIOR HIGH SCHOOLS - Susilawati, Aay; Hernani, Hernani; Sinaga, Parlindungan (International Journal of Education, 2017)
This research aims to determine the effectiveness of project-based learning method using mind maps in science learning for the topic of waste management and its solution to improve students’ environmental attitudes. It adopted a quasi-experimental method with the pretest-posttest control group design. The subjects of the research consisted of the seventh grade students of two classes in one of the private junior high schools in Bandung Regency. The instrument used for data collection was a pretest and posttest on environmental attitudes for students, a questionnaire, and observations of environmental attitudes of the students from peer assessment, teacher’s observations in the school, and parents’ observations at home. The data were analyzed by considering the gain value with its normalization and counting the size effect. The results of the data analysis indicated that gain g = 0.61 for the experimental class and g = 0.41 for the control class, and effect size d = 0.37. These values mean that there were improvements in the students’ environmental attitudes in the school and at home after the application of project-based learning with mind maps. It is concluded that PjBL (Project-Based Learning) method using mind maps for the theme of waste and its management works effectively since it has a small effect on improving students’ environmental attitudes.